PEMILIHAN BATANG BAWAH JARAK PAGAR (Jatropha curcas Linn.) TOLERAN TERHADAP CEKAMAN KEKERINGAN - CHOLID, MOHAMMAD; HARIYADI, HARIYADI; SUSANTO, SLAMET; DJUMALI, DJUMALI; PURWOKO, BAMBANG SAPTA (853-8212)
ABSTRAK